Understanding the Education‐Related Needs of Contemporary Male Veterans. Issue 2 (7th October 2018) - Killam, Wendy K.; Degges‐White, Suzanne
Abstract : Fifteen male veteran college students participated in a qualitative study examining the challenges they experienced while adjusting to college and the supports that facilitated their transitions. Responses revealed 5 common themes: academic challenges; reluctance to seek assistance; difficulty connecting with faculty, staff, and other students; difficulty finding balance in life; and the value of veterans centers on campus.